Dalit Population in India : A Case of Punjab - Kant, Surya (National Geographical Journal of India, 2022)
The paper examines the demographic characteristics, such as size, growth and spatial distribution of Dalit population in Punjab with a focus on inter-caste differences within the Dalit communities. Punjab, the state having the highest share of the Dalit population in India, has the massive size (8.86 million persons in 2011), higher than the total population of Israel. There are 39 castes of the Dalits in the state, but four of these, in combine, subsume nearly three-fourths of total Dalit population. The Mazhabi, the largest Dalit caste with about 30.0 per cent in total Dalit population, was so widely distributed that it made the first ranking caste in the seven of the twenty districts in the state. The same was true of the Chamar, the second largest SC caste. However, the Mahatam, Rai Sikh, notified in 2007, enumerated for the first time in 2011 Census, and ranking at the fifth place among the largest Dalit caste in the state, was highly concentrated in Firozpur district, where it made the first ranking Dalit caste. The Dalits in Punjab were though predominantly rural by residence but quite literate, aware, awakened and dominantly engaged in non-farm economic activities. During 1971-2011, the Dalit population in the state grew at much faster rate than the entire state population. The high growth rate of the Mazhabi and the Bazigar, the two large sized Dalit castes in the state, was a cause of concern, needing priority attention of the policy planners in the state. The Mazhabis, in particular, are predominantly rural by residence, agricultural by occupation and poorly literate, restricting awareness and knowledge